2018
DOI: 10.1177/016146811812001207
|View full text |Cite
|
Sign up to set email alerts
|

Learning Lessons from Instruction: Descriptive Results from an Observational Study of Urban Elementary Classrooms

Abstract: Background For nearly three decades, policy makers and researchers in the United States have promoted more intellectually rigorous standards for mathematics teaching and learning. Yet, to date, we have limited descriptive evidence on the extent to which reform-oriented instruction has been enacted at scale. Purpose The purpose of the study is to examine the prevalence of reform-aligned mathematics instructional practices in five U.S. school districts. We also seek to describe the range of instruction students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Yet, observational studies have shown that instruction in U.S. STEM classrooms tends to be lacking in disciplinary concepts and low in student cognitive demand (e.g., Banilower, Smith, Weiss, & Pasley, 2006; Hiebert et al, 2005; H. C. Hill, Litke, & Lynch, 2018; Kane, Kerr, & Pianta, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, observational studies have shown that instruction in U.S. STEM classrooms tends to be lacking in disciplinary concepts and low in student cognitive demand (e.g., Banilower, Smith, Weiss, & Pasley, 2006; Hiebert et al, 2005; H. C. Hill, Litke, & Lynch, 2018; Kane, Kerr, & Pianta, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Kane & Staiger, 2012), while others rely on standardized protocols to describe instructional practice (e.g. Hill, Litke, & Lynch, 2017). Observational instruments are frequently integrated into observation systems in order to tie instructional quality to student learning outcomes (Gitomer et al, 2014).…”
Section: Objectivesmentioning
confidence: 99%
“…Recently, researchers and instrument developers in mathematics education have begun to use observation tools in service of instructional improvement by featuring them in professional development efforts (e.g. Beisiegel, Mitchell, & Hill, 2017;Hill, Kraft, & Herlihy, 2016;Schoenfeld, 2018). While early evaluation efforts have been promising, these instruments focus on instructional practices in mathematics broadly speaking.…”
Section: Objectivesmentioning
confidence: 99%
“…Although the most appropriate and effective balance of traditional and ambitious mathematics practices is unknown and debated, the mathematics education field calls for greater amounts of ambitious mathematics instruction across K-12 (e.g., NCTM, 2014b; National Governors Association Center for Best Practices, Council of Chief State School Officers (NGA/CCSSO), 2010; National Mathematics Advisory Panel, 2008), and research finds an incorporation of ambitious mathematical practices into teachers' practice is necessary for student improvement, especially during the earlier years of schooling (Barnett, 1995;Chetty et al, 2010;Currie & Thomas, 2000;Kilpatrick et al, 2001). Nonetheless, take-up of ambitious mathematical practices has been modest (e.g., Hiebert et al, 2005;Hill et al, 2018;Kane & Staiger, 2012;Weiss et al, 2003). Though limited in scope, the research base suggests that this take-up may differ based on classroom or school characteristics, such as performance levels of students and demographics of the student population (Boston & Wilhelm, 2017;Desimone & Long, 2010;Smith et al, 2001;Stipek, 2004).…”
Section: Introductionmentioning
confidence: 99%